Juridical Review of the Position of Power of Sale as a Transfer of Land Rights (Analysis of Decision No. 529/PDT/2021/PT SMG) - Anggita, Dewi (Proceedings Series on Social Sciences & Humanities, 2023)
The transfer of land rights can be done through a sale and purchase process by the parties to the agreement. The sale and purchase can be through a power of sale, where the party in the sale and purchase agreement can represent another person through a power of sale to carry out legal actions. In case No. 529/PDT/2021/PT SMG, which had previously been decided by the District Court in decision No. 8/PDT.G/2020, the Plaintiff claimed and stated that he was the legal owner of the lands. However, in practice, the Plaintiff has given and released with a Power of Attorney to Sell and was not considered by the Panel of Judges. This study aims to determine the position of Power of Sale in Indonesian treaty law and to determine whether a Power of Sale can be the basis for the transfer and replacement of land rights. The method used in this research is normative juridical legal research using Library Research techniques. The results of the research findings reveal that based on Article 1792 of the Civil Code formulates the granting of power of attorney as an agreement between a person as a grantor with another person as a proxy, to carry out an act or action on behalf of the grantor. So that this power of sale can also be used in terms of land transfer.